The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s1535-6108(02)00016-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a conditional AML1-ETO oncogene bypasses embryonic lethality and establishes a murine model of human t(8;21) acute myeloid leukemia

Abstract: The AML1/CBFbeta transcription factor complex, a frequent target of chromosomal translocations in leukemia, is essential for the generation of definitive hematopoietic stem cells. Paradoxically, expression of the acute myeloid leukemia-associated AML1-ETO fusion protein in mice results not in leukemia, but in embryonic lethality due to an absence of normal hematopoiesis. To bypass the embryonic lethality, we generated a mouse strain with a conditional AML1-ETO knockin allele that contains a loxP bracketed tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
362
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(399 citation statements)
references
References 41 publications
36
362
1
Order By: Relevance
“…However, no disease was developed in EHKI DNeo mice during the long-term observation period (Figure 2a, thin lines), indicating that the acquired expression of E2A-HLF per se is insufficient for the development of leukemia. This finding is in line with previous reports showing that iKI mice of other leukemogenic transcription factor chimeras, such as AML1-ETO and MLL-CBP, did not show hematopoietic disorders, and secondary mutations induced by N-methyl-N-nitrosourea or irradiation were required to induce a fully malignant phenotype (Higuchi et al, 2002;Wang et al, 2005). In this study, to introduce additional gene alterations, we used RIM, as it not only …”
Section: Discussionsupporting
confidence: 85%
“…However, no disease was developed in EHKI DNeo mice during the long-term observation period (Figure 2a, thin lines), indicating that the acquired expression of E2A-HLF per se is insufficient for the development of leukemia. This finding is in line with previous reports showing that iKI mice of other leukemogenic transcription factor chimeras, such as AML1-ETO and MLL-CBP, did not show hematopoietic disorders, and secondary mutations induced by N-methyl-N-nitrosourea or irradiation were required to induce a fully malignant phenotype (Higuchi et al, 2002;Wang et al, 2005). In this study, to introduce additional gene alterations, we used RIM, as it not only …”
Section: Discussionsupporting
confidence: 85%
“…It may be a common underlying mechanism for the pathogenesis in AML1-associated leukemia. However, recently generated transgenic or knock-in mice showed that AML1 mutations are critical for the development of AML, but that one or more additional mutations are necessary for leukemogenesis [10][11][12]. This accepted hypothesis is supported by the cytogenetic findings in the case of our patient exhibiting a complex karyotype.…”
supporting
confidence: 69%
“…, 2004). RUNX1-ETO expression in conjunction with treatment with the mutagen N-ethyl-N-nitrosourea (ENU) resulted in myeloid leukemia or granulocytic sarcoma (Yuan et al, 2001;Higuchi et al, 2002). Therefore, RUNX1-ETO is able to predispose myeloid precursors to transformation.…”
Section: Discussionmentioning
confidence: 99%